UV-curable silicone materials with tuneable mechanical properties for 3D printing. (July 2021) - Foerster, Aleksandra; Annarasa, Vinotharan; Terry, Anna; Wildman, Ricky; Hague, Richard; Irvine, Derek; De Focatiis, Davide S.A.; Tuck, Christopher
Graphical abstract: Highlights: Novel UV-curable, highly flexible silicone compositions which are suitable for use in a valve-based jetting process were developed. Developed materials were characterised using FTIR, DSC, TGA and uniaxial tensile tests. It was shown that the mechanical properties were strongly dependent on the composition and that the stiffness could be made to vary from ~50 kPa to ~180 kPa. An EV model demonstrated a growth in the network density and a drop in the limiting extensibility with increasing silicone content. Abstract: In this paper, we present the development of a family of novel, UV-curable, highly flexible, 3D printable silicone-based materials, the mechanical properties of which can be tuned simply by varying the ratio of the polymerisable reagents within the formulation. This tuneability is achieved by exploiting the balance between in-cure phase separation and differential reactivity within the formulation to successfully produce composite structures via both casting and valve-based jetting processes. The structure and properties of both cast and 3D printed materials were examined in a range of compositions of silicone to acrylate between 30:70 and 70:30. The phase segregated structure, evidenced from distinct glass transitions, and the thermal stability of these materials were both shown to be insensitive to the composition ratio, whereas the elastic properties were strongly dependent on the composition. The stiffness could be made to vary from ~50 kPa to ~180 kPa by increasing the silicone content. This study will guide the formation of a new generation of Additive Manufacturing (AM) silicone elastomeric functional structures for various applications ranging from flexible electronics to regenerative medicine, which will benefit from local changes in mechanical properties within the same material family.